(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
The increasing prevalence of mental health disorders in contemporary society necessitates a re-evaluation of dominant frameworks of mental wellbeing. Modern psychological and biomedical models, while effective in clinical contexts, often neglect the ethical and spiritual dimensions of human existence. Indian Knowledge Systems (IKS) offer a holistic paradigm that integrates physical, mental, ethical, and spiritual aspects of wellbeing. This paper explores the concept of mental wellbeing through the lens of Jain philosophy, a profound and systematic tradition within IKS. Drawing upon primary texts such as the Tattvārthasūtra, Ācārāṅgasūtra, and Samayasāra, the study analyses key concepts including karma theory, kaṣāyas (passions), ahiṃsā (non-violence), and aparigraha (non-possessiveness). It argues that Jain philosophy conceptualizes mental wellbeing as a state of inner purity achieved through ethical discipline, self-regulation, and detachment. The study further highlights the relevance of Jain principles in addressing contemporary challenges such as stress, anxiety, consumerism, and ethical decline. The paper concludes that integrating Jain philosophical insights into modern mental health discourse can contribute to a more sustainable and holistic model of wellbeing.